2017
DOI: 10.2134/agronj2017.05.0247
|View full text |Cite
|
Sign up to set email alerts
|

Planting Date, Maturity, and Temperature Effects on Soybean Seed Yield and Composition

Abstract: Core Ideas Planting date and maturity group decisions can greatly affect yield and composition. Temperature had a significant effect on seed yield and composition. Planting date × maturity group should be chosen based on the product's end use. Soybean [Glycine max (L.) Merr.] production has greatly increased in the upper U.S. Midwest over the last decade, but little information exists regarding the interactive effects of environment and spring management decisions on soybean seed yield and composition. Our obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
63
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(96 citation statements)
references
References 26 publications
16
63
4
Order By: Relevance
“…Inconsistent effects of seeding date on protein concentration have been reported from Quebec (Tremblay et al., 2006). Cultivar had little effect on seed protein concentration, accounting for <1% of the total variance, and is consistent with a study in Wisconsin that explored the same in soybean maturity groups from 0.6 to 2.0 (Mourtzinis et al., 2017). The lowest protein concentration occurred at Portage17, which received the lowest rainfall throughout the growing season and specifically in August which corresponded with the seed‐fill period.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Inconsistent effects of seeding date on protein concentration have been reported from Quebec (Tremblay et al., 2006). Cultivar had little effect on seed protein concentration, accounting for <1% of the total variance, and is consistent with a study in Wisconsin that explored the same in soybean maturity groups from 0.6 to 2.0 (Mourtzinis et al., 2017). The lowest protein concentration occurred at Portage17, which received the lowest rainfall throughout the growing season and specifically in August which corresponded with the seed‐fill period.…”
Section: Resultssupporting
confidence: 87%
“…(2006) in Quebec and partially agree with Mourtzinis et al. (2017) who found seed oil concentration to be mainly affected by seeding date (lower oil with late seeding) and to a lesser degree by maturity grouping. Temperature during seed filling has been related to regional soybean seed oil concentrations in Minnesota such that oil increases at a rate of 6.6 g kg −1 °C −1 (Naeve & Huerd, 2008).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Using protein as a gauge of soybean value assumes that the relative abundance of amino acids is static. However, numerous reports on both whole soybean and soybean meal have shown that the relative abundance of some or all of the five limiting amino acids within the protein is negatively correlated with protein (Thakur and Hurburgh, 2007;Medic et al, 2014;Warrington et al, 2015;Miller-Garvin and Naeve, 2016;Mourtzinis et al, 2017). A characterization of a decade of US soybean sample analysis showed that the amino acid balance of all five limiting amino acids decreased with increased protein concentration, and the balance was made up by increased relative abundance of glutamic acid and arginine within the protein (Medic et al, 2014).…”
mentioning
confidence: 99%